Asymptomatic Esophageal Eosinophilia in an 11-Year-Old with Severe Persistent Asthma - Casey E. Hofstaedter; Runa Watkins; Nidhi Kotwal (Case Reports in Pediatrics)
Asymptomatic esophageal eosinophilia (aEE) is a rare presentation, where patients have increased eosinophils in esophageal mucosa but lack any esophagus-related symptoms. Cases of aEE have only been documented in adults, and little is known about its clinical significance and whether treatment is warranted. We report a case of an 11-year-old patient with uncontrolled severe persistent asthma who underwent flexible bronchoscopy and upper endoscopy as a part of complete aerodigestive evaluation. Elevated intraepithelial eosinophils in the esophageal mucosa were noted, suggesting an aEE-like presentation. This case documents a pediatric patient with aEE and highlights the importance of combined aerodigestive assessment with pulmonology and gastroenterology teams for the evaluation of severe asthma.